Enhancing ESG Performance in Islamic Banks: The Impact of Shari’ah Governance Quality Across Countries - Milena, Wannes; Stefan, Alberto (Journal International Economic Sharia, 2024)
Objective; The purpose of this study is to examine the effect of Shari’ah governance quality on Environmental, Social, and Governance (ESG) performance in Islamic banks, contributing to the understanding of governance structures in promoting sustainability practices.Methods; A quantitative method was employed in the form of multiple regression analysis on the data of a sample of Islamic banks. The study investigated the linkage of Shari’ah governance quality, Shari’ah supervisory board size, operational structures and ESG performance in environmental, social and governance dimensions.Results; The results show that Shari’ah governance quality leads to a significant improvement in ESG performance with improvement in all dimensions. The number of members on the Shari’ah supervisory board and operational frameworks positively affect ESG outcomes as well. In contrast, little impact on ESG performance was detected when segmented by bank size and market capitalization.Novelty; The study contributes by shedding light on the underexplored aspect of governance through Shari’ah governance as a driver for achieving sustainable practices in the Islamic banking context.Research Implications; The research contributes to enhancing ESG performance in Islamic banks by highlighting the importance of Shari’ah governance, Nigerian policymakers and bank managers striving for convergence of Islamic banking and global sustainability objectives could benefit greatly from the study.